Job satisfaction status among Bachelor degree nurses working at a tertiary level hospital, Nepal - Subedi, Pabitra; Shrestha, Sulochana (Journal of Chitwan Medical College, 2026)
Introduction: Nurses are key frontline healthcare professionals, and their job satisfaction critically influences patient care quality. This study aimed to determine job satisfaction status among bachelor's degree nurses at a tertiary-level hospital in Nepal. Method: A descriptive cross-sectional study was conducted at Tribhuvan University Teaching Hospital, Kathmandu, from 02 Jul to 28 Jul 2017. The study population comprised all 254 bachelor's degree nurses (BN/BNS or BSc Nursing) with 1-10 years of experience. Using simple random sampling, 136 nurses were selected. Data were collected via a self-administered, semi-structured questionnaire based on Herzberg's Two-Factor Theory, assessing eight job dimensions. The tool's reliability was good (Cronbach's alpha=0.80). Ethical approval was obtained from the Institutional Review Board of the Institute of Medicine. Data were analysed using SPSS version 20. Descriptive statistics and chi-square test were used, with p<0.05 considered significant. Result: Out of 136 sampled nurses, 132 participated (97.1%). More than half, 79(59.8%), were satisfied with their job. The highest contributing factor was supervision (20.47±4.86), while the lowest was work itself (10.88±2.52). There was no statistically significant association between job satisfaction and socio-demographic variables (p>0.05 for all). Conclusion: Although a majority of nurses reported satisfaction, a substantial proportion (40.2%) were dissatisfied. The findings highlight areas for improvement, particularly in making the work itself more rewarding and addressing growth opportunities.